An approach to support legacy systems reengineering to MDD using metaprogramming - Papotti, P. E.; do Prado, A. F.; de Souza, W. L. (2012 XXXVIII Conferencia Latinoamericana en Informatica, 2012)
Model-Driven Development (MDD) has been a subject of several studies focused on software development. Most studies in this area aims to show how to transform domain models, designing and implementing applications running on different architectures. However, a problem is related to develop a practical approach to support the reengineering of a legacy application for an MDD application. This paper presents an approach for Software Reengineering of a legacy application using MDD and metaprogramming. In Reverse Engineering, we obtain a object-oriented model based on legacy application code and database and, in Forward Engineering, the object-oriented model is refined and used as basis to metaprograms perform code generation. The proposed approach was evaluated through the reengineering of a real legacy system in academic domain from a database with 155 tables.